ESP Material for Maritime Affairs and Fisheries School in Indonesia - Tahang, Heriyanti; Manuputty, Rensi; Uluelang, Kris; Yuliana, Yuliana (International Journal of Language Education, 2021)
Identifying English for Specific Purposes material for A Specific Student was the process of selecting, adjusting, and evaluating English material based on the special needs of students. Need analysis is needed to identify ESP learning material. The purpose of this research was to identify the English for Specific Purpose (ESP) Materials need by students in learning the English Language for Students in Maritime Affairs and Fisheries School using mix method. Through the Cluster Random Sampling, thirty-six students of fisheries product processing technology department level II at Sekolah Usaha Perikanan Menengah (SUPM) Negeri Sorong became the sample of this research. Guttman scale questionnaires and interviews were used to collect the Data. Questionnaires were given to students to find out the goals, necessities, want, and lack of students. To do the triangulation method, the interview was conducted to deeper explanation gather from the Questionnaires’ answer. The results showed that ESP Material need by the students in the fisheries product processing technology department was English learning material that related to fisheries product processing technology in order students can use the language when having a job. While the ESP topics that students were expected to learn are about the duties of a captain, special terms in shipping, special terms of fisheries, ways to operate machinery, conversations about fisheries, ways to bind fish, special terms for a cook and others English materials are correlated with fisheries product processing technology department.